THE PROBLEM OF THE POSITION OF CIVIL SERVANTS IN ELECTIONS AND ELECTIONS PERSPECTIVE LAW NO. 7 OF 2017 JO LAW NO. 20 OF 2023 - Soegianto; Retno Widyani; Aan jaelani; Usman (Jurnal Abdisci, 2024)
The purpose of community service activities is to socialize the problem of the position of civil servants in elections and elections from the perspective of Law No. 7 of 2017 and Law No. 20 of 2023. The socialization will be held at Satpol PP Cirebon City on December 5, 2023. The socialization material presented was related to the problem of the position of civil servants in the 2024 Elections and Elections, what civil servants can and cannot do to maintain civil servants' neutrality following Law No. 5 of 2014 and Law No. 20 of 2023 concerning civil servants. The sanction of non-neutrality of civil servants will be removed from office and cause a blunder because campaigns can be carried out in schools, campuses, and government facilities, but not in places of worship. It is time to mature in the nation and state by accepting differences and working together, not alone but in a hostile manner. The 2024 democracy party is expected to take place with great joy.